Syncretic Religiosity in Punden Folklore: The Continuity of Islamic–Javanese Values in Rural Java, Indonesia - Khoirul Muttaqin; Ma'murjon Abdurasulov; Layli Hidayah; Itznaniyah Umie Murniatie; Prayitno Tri Laksono (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2025)
This study aims to examine the role of punden folklore in preserving and transmitting the religious, moral, and social values of rural Javanese Muslim communities, particularly in Dukun Subdistrict, Gresik, Indonesia. This research is significant because the punden tradition represents a form of local religiosity that harmoniously integrates Islamic teachings with Javanese cultural practices, reflecting a dynamic synthesis between Islam and indigenous wisdom. The study employs a qualitative method, with data collected through observation and in-depth interviews involving local residents, religious leaders, and custodians of sacred sites. The findings reveal that punden folklore functions as a living value system that sustains the religious and social life of the Dukun community. First, pilgrimages and veneration of saintly figures such as Mbah Asyari and Mbah Banjur instill values of devotion, spiritual remembrance, and ta’dhim (reverence) as expressions of lived religiosity. Second, sedekah bumi and pilgrimage rituals demonstrate a harmonious integration of Islamic practices with Javanese cultural symbols such as flower scattering, incense, wayang, and pencak silat. Third, these traditions function as moral education and social adhesive that cultivate patience, sincerity, and humility while reinforcing guyub rukun (social harmony) and ecological awareness across generations. In practical terms, the study affirms that the punden tradition serves not only as an element of intangible cultural heritage but also as a social and religious mechanism that strengthens community resilience. The originality of this research lies in its integrative approach, which positions punden folklore as a living social and spiritual practice, offering new insights into Islamic–Javanese syncretism and the preservation of religious cultural heritage in Indonesia.